PUBLIC HEALTH POLICY RESPONSES TO AIR POLLUTION IN INDIA: CHALLENGES AND STRATEGIES FOR SUSTAINABLE DEVELOPMENT - Sah, Suresh Kumar (Alqaprint Jatinangor, 2024)
This study investigates the public health policy responses to air pollution in India, highlighting the challenges and strategies needed for sustainable development. Despite significant efforts to address air pollution through policies such as the National Clean Air Programme (NCAP), the effectiveness of these measures remains limited. The research involved a systematic review of existing literature, policy documents, and case studies from various Indian cities. Data were collected from government reports, academic journals, and interviews with public health and environmental experts. Key findings indicate persistent issues with policy enforcement, inadequate public awareness, and insufficient coordination among agencies. These challenges impede the achievement of meaningful reductions in air pollution levels and improved public health outcomes. The study emphasizes the need for more comprehensive and robust policy frameworks to address these issues effectively. Recommendations include enhancing policy implementation, increasing public engagement, and leveraging advanced technologies for air quality monitoring and management. Addressing these gaps is crucial for advancing sustainable development and mitigating the adverse health impacts of air pollution. The research provides actionable insights for policymakers and stakeholders aiming to improve air quality and public health in India.